Strategy Implementation and Performance of Manufacturing Pharmaceutical Companies in Kenya - Njeru, Simon Kinyua; Mang’ana, Robert; Anene, Enos (Journal of Business and Strategic Management, 2025)
Purpose: The current study aimed to investigate the extent to which strategy implementation affects organizational performance in Kenyan pharmaceutical manufacturers, Methodology: A census sample of all 20 pharmaceutical manufacturing companies registered in Kenya at the time of this research was used. Questionnaire data was used to collect data from 74 respondents sampled purposively from to ensure they met the pre-defined inclusion criteria. A linear regression model comprising resource allocation, effective communication, employee support and training, and strategic leadership as the constructs of the independent variable strategy implementation was the basis of statistical analysis to estimate influences of strategy implementation factors on the dependent variable, organizational performance. Findings: Effective communication (p-value = 0.000) and resource allocation (p-value = 0.001) significantly impact organizational performance. Employee support and training (p-value = 0.044) also contribute, but less so. Strategic leadership (p-value = 0.260) was not significant, suggesting leadership effectiveness depends on contextual factors like culture, size, and structure. Unique Contribution to Theory, Practice and Policy: Based on these findings, it is recommended that pharmaceutical manufacturing firms in Kenya prioritize effective communication and strategic resource allocation as key drivers of organizational performance. They should consider adopting targeted communication strategies for clarity and alignment, besides robust financial planning to direct resources toward high-impact initiatives. Moreover, the firms should ensure that employee support and training complement communication and resource allocation strategies. Lastly, companies should evaluate their strategic leadership structures, based on the realization that their impact may vary based on contextual factors such as organizational culture and structure.